STRATEGI KOMUNIKASI YAYASAN GAYA DEWATA DALAM SOSIALISASI LAYANAN VCT DI KALANGAN GAY - Silvia, Dinna Rafika; Sugiarica Joni, I Dewa Ayu; Pascarani, Ni Kadek Dewi (E-Jurnal Medium, 2017)
ABSTRAK HIV / AIDS nowadays is a growing disease and a global problem that has swept the world since 1981. Gay is a vulnerable group to HIV / AIDS transmission. One of the active organizations in Bali in prevention of HIV / AIDS especially for gay community is Yayasan Gaya Dewata. This organization has been active in preventive action for twenty years. The vigorous activity at the Gaya Dewata Foundation is to socialize the Voluntary Counseling and Testing (VCT) services to reduce the HIV / AIDS transmission rate. To gain successful result from the target, preparation of communication strategy is very important thing to be done in order to achieve an objective of organization. Hence, this research aimed to figure out communication strategy of Yayasan Gaya Dewata in socializing Service Voluntary Counseling and Testing (VCT); thus, gay oriented people who’s tend to close themselves, finally willing to do Voluntary Counseling and Testing (VCT). This research use qualitative research method using semi-structured interview data collection techniques, observation, and documentation study. Based on the findings in the field, it reflects that Yayasan Gaya Dewata uses several steps in formulating communication strategy before disseminating Voluntary Counseling and Testing (VCT) services, from knowing audiences, compiling messages, setting methods, to selecting media usage. Keywords: Communication Strategy, HIV/AIDS, LGBT, Voluntary Counseling and Testing.